Performance Analysis of a Laboratory-Scale Wind Turbine: Blade Angle and Its Effect on Efficiency - Taufik Ulhakim, Muhamad; Syafari, Muhammad Muhtar; Sukarman, Sukarman (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2024)
A wind turbine power plant (WTPP) is a renewable energy system that harnesses wind energy to generate electricity. Indonesia has been identified as a region with considerable wind energy potential, making it a promising location for developing this technology. In alignment with this potential, the Indonesian government has set a target of approximately 7 GW of installed wind turbine capacity by 2030. This study examines the influence of blade angle on the efficiency of electrical energy generation. Three blade angle variations—20°, 30°, and 40°—were analyzed using an experimental setup featuring a horizontal-axis wind turbine with five blades and a constant wind speed of 6.2 m/s. The rotation of the blades converts wind energy into kinetic energy, which is subsequently transferred to a generator to produce electricity. Experimental investigations were conducted using a laboratory-scale prototype, revealing that a blade angle of 40° achieved the highest efficiency. Specifically, the turbine exhibited an efficiency of approximately 29% after 3 minutes of rotation, which increased to 42% after 8 minutes. These findings highlight the pivotal role of blade angle optimization in enhancing WTPP performance. Moreover, this study provides a valuable reference for advancing wind energy applications in Indonesia, supporting the transition towards more sustainable and efficient renewable energy solutions.